P280 A Single Centre Experience Of Spontaneous Clearance Of Mycobacterium abscessus In Cystic Fibrosis Patients. (12th November 2015) - Green, HD; Barry, PJ; Bright-Thomas, R; Brennan, AM; Webb, AK; Lord, R; Horsley, A; Jones, AM
Abstract : Introduction: The Mycobacterium abscessus complex is an emerging group of pathogens, which pose significant management challenges in CF. Current guidelines specify treatment is indicated in patients with repeated sputum culture positivity alongside radiological or clinical deterioration. However, identifying NTM as the cause of deterioration in the polymicrobial CF lung is challenging. Additionally, M. abscessus complex isolates are usually multi-resistant, requiring lengthy and complex treatment regimens. Whether to treat patients based on culture results alone is contentious and approaches differ between centres. Here we analyse our experience of M. abscessus at a large UK adult CF centre. Methods: All patients with 1 or more positive sputum culture for M. abscessus since 2010, and minimum of 1 mycobacterial culture and 1 year of follow-up since first positivity were included. Anti-mycobacterial treatment and culture results following first positivity were recorded. M. abscessus eradication was defined as 4 consecutive negative cultures spanning at least 1 year. Results: 21 patients were included. Of these, 6 (29%) have received/are receiving, anti-mycobacterial therapy based on clinician diagnosis of M. abscessus pulmonary disease. All 6 currently remain culture positive. Of the 15 remaining patients, 6 are consistently culture positive (duration 12 months - 5 years), but do not have evidence of NTM pulmonary disease. Spontaneous clearance of M. abscessus from sputum has occurred in 7 patients (Table 1 ). Of these, 5 (71%) had ≥3 positive cultures including 1 patient with 5 positive samples spread over 2 years and 1 patient with 5 positive samples spread over 9 months. In 2 patients infection status cannot yet be confirmed as these patients have ≤4 mycobacterial culture results following their initial positive result. Conclusion: Patients may spontaneously clear M. abscessus from their sputum, even with a history of multiple positive cultures over many months. If patients are treated on culture results alone there is a risk of initiating potentially unnecessary, lengthy and poorly tolerated treatment. Our results suggest that adhering to clinical guidelines of recognising clinical deterioration secondary to M. abscessus remains paramount before commencing treatment and assessment of treatment success without control data may be very misleading.